Empowering Farmers in Sub-Saharan Africa : Best Practices - Beaudoux, Elaine; Bourque, Andre; Collion, Marie-Helene; Delion, Jean; Gentil, Dominique; Kabuga, Charles; Schwettman, Jurgen; Shah, Ashih (World Bank, Washington, DC, 2012)
This article previews a study defining "farmer empowerment" (increasing the capacities of disadvantaged people to move out of poverty). The study discusses specific country case studies (Uganda, Nambia, Cameroon, Burundi, Mali, and Madagascar) and their dealings with farmer organizations and practices.